2005
DOI: 10.1111/j.1460-9568.2005.03977.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel cytosolic RING finger protein dactylidin is up‐regulated in brains of patients with Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by a progressive degeneration of neurons along with deposition of amyloid plaques and the formation of neurofibrillary tangles. Neurodegeneration in AD follows both a spatial pattern of selective vulnerability and temporal staging of affected neurons. In order to address transcriptional changes associated with this selective vulnerability, we used subtractive hybridization of transcripts derived from human frontal cortex, which degenerates in late stages of AD, against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…It is up-regulated in the inferior temporal lobes of Alzheimer disease patients compared with healthy controls [133].…”
Section: Discussionmentioning
confidence: 99%
“…It is up-regulated in the inferior temporal lobes of Alzheimer disease patients compared with healthy controls [133].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of candidate genes could provide easily accessible biomarkers to monitor Alzheimer's, and these are SORL1, and APP, and APOE, the other 21 genes listed are related to other diseases but may also be found to be associated with Alzheimer's; these are transmembrane protein 59 [11], chaperonin containing TCP1 subunit 4 (delta) [12], insulin-like growth factor 2 receptor [13], splicing factor proline/glutamine-rich [14], peroxiredoxin 3 [15], ring finger protein 14 [16], iduronate 2-sulfatase [17], single-stranded DNA-binding protein 1 [18], spectrin repeat containing, nuclear envelope 2, thioredoxin-like 4A [19], syntaxin-binding protein 3 [20], SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily a, member 1, unc-51-like kinase 2 ( C. elegans ), ATP/GTP-binding protein 1, fatty-acid-binding protein 7, brain [21], calbindin 1, 28 kDa [22], H2A histone family, member Y [23], coatomer protein complex, subunit alpha [12], Sin3A-associated protein, 18 kDa [24], 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase, and synaptotagmin-binding, cytoplasmic RNA-interacting protein [25]. …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A systematic search for downstream regulators of parthanathos identified RNF146 (also termed "Iduna") (9). In an independent line of studies, RNF146 (in this study, it was also called "dactylidin") was simultaneously identified as a differentially expressed protein in the vulnerable regions of the brain in Alzheimer's disease; in this study, its E3 ubiquitin ligase function was also suggested (18). The initial functional role of RNF146 was first demonstrated in neuronal models of cell death induced by NMDA receptor agonists.…”
Section: Discussionmentioning
confidence: 70%